Neurons but not glial cells overexpress ubiquitin in the rat brain following focused ultrasound-induced opening of the blood-brain barrier - Alonso, Angelika; Reinz, Eileen; Fatar, Marc; Jenne, Jürgen; Hennerici, Michael G.; Meairs, Stephen (Neuroscience, 2010)
Focused ultrasound-induced opening of the blood-brain barrier (BBB) in the presence of ultrasound contrast agents is a promising strategy for a targeted drug delivery to the brain. The aim of our study was to identify whether brain molecular stress pathways are targeted by ultrasound treatment. Using an upper level of acoustic pressures in combination with microbubbles, which have been previously reported as reliable for BBB opening without causing tissue damage, we found that ultrasound leads to an increased ubiquitinylation of proteins in neuronal (11±3 ubiquitin-overexpressing cells per optical field) but not glial cells 6 h post-insonation, increasing to 16 (±4) labelled cells after 24 h. No changes in the expression of Hsp70 and Hsc70 were detected over 24 h. Ultrasound treatment was followed by limited apoptosis after 24 h (32±6 cleaved-caspase 3-positive cells per optical field) in the insonated areas. Only neurons were identified in the apoptotic population. Although these observations may not be applicable for all acoustic parameters useful for BBB opening, they demonstrate that insonation of the rat brain with the parameters used in our experiments is a useful tool for BBB opening and induces specific cellular stress response restricted to neuronal cells.
Gesehen am 17.03.2021